(untitled) (NAU Journal of Technology and Vocational Education, 2024)
To carry out this study, one research question was raised and two null hypotheses were testedat a0.05 level of significance. The study adopted a descriptive survey research design. The sampleconsisted of 500 small-scale business owners out of 1504 small-scale businesses in Anambra Statewhich were selected using purposive and convenience sampling techniques. The instrument for datacollection was a validated self-administered questionnaire. Cronbach’s alpha formula was usedtodetermine the internal consistency of the questionnaire which yielded an a reliability coefficient of 0.84. The researchers administered the instrument with the help of five research assistants totherespondents. Mean and standard deviation were used to answer the research question and determinethe homogeneity or otherwise of the respondents while a t-test was used for testing the null hypotheses. The findings of the study revealed that financial reporting and analysis practices werelowly adopted by small-scale business owners for business growth in Anambra State. Irrespective of their gender and period of existence in the marketplace, small-scale business owners do not differ significantly in their mean ratings on the extent they adopt financial reporting and analysis practices for business growth. The study concluded that small-scale business owners in Anambra State will not have detailed information about the financial strengths and weaknesses of their business empires as aresult of their under-utilization of financial reporting and analysis practices in the day-to-day runningof their business operations. It was recommended among others that small-scale business owners should undertake technical seminars and workshops to improve their awareness and knowledge of financial reporting and analysis practices. This would encourage them to make use of financial reporting and analysis practices in their business to have a better view of the profitability of their business in Anambra State.